2018
DOI: 10.1152/ajpregu.00201.2017
|View full text |Cite
|
Sign up to set email alerts
|

Rag1-null Dahl SS rats reveal that adaptive immune mechanisms exacerbate high protein-induced hypertension and renal injury

Abstract: The present study, performed in Dahl salt-sensitive (SS) and SS- Rag1 rats lacking T and B lymphocytes, tested the hypothesis that immune cells amplify salt-sensitive hypertension and kidney damage in response to a high-protein diet. After being weaned, SS and SS- Rag1 rats were placed on an isocaloric, 0.4% NaCl diet containing normal (18%) or high (30%) protein. At 9 wk of age, rats were switched to a 4.0% NaCl diet containing the same amount of dietary protein and maintained on the high-salt diet for 3 wk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
(49 reference statements)
1
33
0
1
Order By: Relevance
“…Additionally, nutrition and dietary factors have a tremendous impact on immune function and the host's ability to separate and protect itself from its environment [38][39][40] , and the role of the immune system in the development and amplification of Dahl SS hypertension is wellestablished 41 . Recent studies in our laboratory utilizing the SS Rag1−⁄− rat, an SS rat lacking functional T and B lymphocytes, demonstrate a clear role for immune mechanisms in the exacerbation of high dietary protein-induced hypertension and renal damage 13 . While decades worth of evidence has revealed the extensive effects of nutrition on all aspects of immunity [42][43][44] , more recent studies have demonstrated postprandial induction of both physiological and pathological inflammatory processes, offering a potential mechanism whereby changes in dietary intake can alter functional phenotypes [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, nutrition and dietary factors have a tremendous impact on immune function and the host's ability to separate and protect itself from its environment [38][39][40] , and the role of the immune system in the development and amplification of Dahl SS hypertension is wellestablished 41 . Recent studies in our laboratory utilizing the SS Rag1−⁄− rat, an SS rat lacking functional T and B lymphocytes, demonstrate a clear role for immune mechanisms in the exacerbation of high dietary protein-induced hypertension and renal damage 13 . While decades worth of evidence has revealed the extensive effects of nutrition on all aspects of immunity [42][43][44] , more recent studies have demonstrated postprandial induction of both physiological and pathological inflammatory processes, offering a potential mechanism whereby changes in dietary intake can alter functional phenotypes [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies found that the source of protein in the diet was largely responsible for this phenotype in the grain-fed SS rats since substitution of casein in the purified diet with wheat gluten recapitulated the protective phenotype 10 . Furthermore, a high protein (casein) diet exacerbates SS hypertension, which is mediated primarily via immune mechanisms 11,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes/macrophages can also scavenge reactive oxygen species (Rosenblat et al, 2013) and have a role in clearing vasoactive peptides such as endothelin-1 (Czopek et al, 2019), influencing local vasomotor tone and blood pressure. Depletion of monocytes/macrophages, or impairing their ability to clear endothelin-1, increases blood pressure over a few days in humans and mice (Guzik et al, 2007;Abais-Battad et al, 2018), particularly in the setting of a pre-existing challenge to blood pressure such as high salt or Ang II infusion. Conversely, T-cells and B-cells depletion are protective, reducing hypertension and vascular free-radical production in experimental models (Guzik et al, 2007;Abais-Battad et al, 2018).…”
Section: Inflammationmentioning
confidence: 99%
“…Depletion of monocytes/macrophages, or impairing their ability to clear endothelin-1, increases blood pressure over a few days in humans and mice (Guzik et al, 2007;Abais-Battad et al, 2018), particularly in the setting of a pre-existing challenge to blood pressure such as high salt or Ang II infusion. Conversely, T-cells and B-cells depletion are protective, reducing hypertension and vascular free-radical production in experimental models (Guzik et al, 2007;Abais-Battad et al, 2018). Thus, these cells of the adaptive immune system appear to be "pro-hypertensive" and experimentally, re-population of the T-cell pool restores the full hypertensive response to chronic Ang II infusion (Fehrenbach et al, 2020).…”
Section: Inflammationmentioning
confidence: 99%